2021
DOI: 10.48550/arxiv.2102.02832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Observational Difference Between the Accretion Disk-Corona Connections among Super- and Sub-Eddington Accreting Active Galactic Nuclei

Hezhen Liu,
B. Luo,
W. N. Brandt
et al.

Abstract: We present a systematic X-ray and multiwavelength study of a sample of 47 active galactic nuclei (AGNs) with reverberation-mapping measurements. This sample includes 21 super-Eddington accreting AGNs and 26 sub-Eddington accreting AGNs. Using high-state observations with simultaneous X-ray and UV/optical measurements, we investigate whether super-Eddington accreting AGNs exhibit different accretion disk-corona connections compared to sub-Eddington accreting AGNs. We find tight correlations between the X-ray-to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 165 publications
(310 reference statements)
1
3
0
Order By: Relevance
“…This value is in perfect agreement with the dimensionless accretion rate from Du et al (2014). However even assuming the luminosity from Liu et al 2021, with which the value of the accretion rate would be 𝜆 Edd ∼ 4.40, the source would remain a super-Eddington accreting AGN. IRAS 04416+1215 turned out to be the most peculiar of our sample, it is classified as NLS1 galaxy, showing narrow H𝛽 line (FWHM=1670 km s −1 , Moran et al 1996) and very broad [OIII] (FWHM=1150 km s −1 , Véron-Cetty et al 2001) lines, which is typically found in sources accreting at such high Eddington accretion rates (Greene & Ho 2005;Ho 2009).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This value is in perfect agreement with the dimensionless accretion rate from Du et al (2014). However even assuming the luminosity from Liu et al 2021, with which the value of the accretion rate would be 𝜆 Edd ∼ 4.40, the source would remain a super-Eddington accreting AGN. IRAS 04416+1215 turned out to be the most peculiar of our sample, it is classified as NLS1 galaxy, showing narrow H𝛽 line (FWHM=1670 km s −1 , Moran et al 1996) and very broad [OIII] (FWHM=1150 km s −1 , Véron-Cetty et al 2001) lines, which is typically found in sources accreting at such high Eddington accretion rates (Greene & Ho 2005;Ho 2009).…”
Section: Introductionsupporting
confidence: 74%
“…In this campaign we are carrying out to study the broadband X-ray properties of super-Eddington AGN, all the sources have new NuSTAR observations performed simultaneously with XMM-Newton or Swift-XRT. IRAS 04416+1215 has bolometric luminosity log(𝐿 bol /erg s −1 ) = 47.55, according to Castelló-Mor et al 2016 and log(𝐿 bol /erg s −1 ) = 45.52 according to Liu et al 2021. The former estimate is computed using, for the spectral energy distribution (SED) fitting procedure, the Slone & Netzer (2012) code, including the comparison of the observed SED with various combinations of disc SEDs covering the range of mass, accretion rate, spins and taking into account the correction for intrinsic reddening and host-galaxy contribution.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the correlations of the data in Figure 5 (and Table 2) indicate that 𝛼 ox correlates as strongly with He EW as it does with 𝐿 2500 , if not slightly more so, which is a notable result given that previous investigations have been unable to find another parameter that correlates as strongly with 𝛼 ox as 𝐿 2500 (e.g. Shemmer et al 2008;Liu et al 2021).…”
Section: The Interdependence Of 𝛼 Ox 𝐿 2500 and He Ewmentioning
confidence: 64%
“…2. Absorption on scales smaller than most of the accretion disk (e.g., due to a thick inner disk, a "failed wind", or the outflowing material itself in the case of radiation-pressure confinement; e.g., Proga & Kallman 2004;Baskin et al 2014;Ni et al 2018;Liu et al 2021) can absorb the X-ray photons from the hot corona, leaving the UV emission from the accretion disk largely unaffected, thus resulting in significant X-ray weakness observed for type 1 QSOs. 3.…”
Section: X-ray Weakness Of Pso167-13mentioning
confidence: 99%